The Impact of Organizational Culture, Compensation on Job Satisfaction, and Work Motivation on School Principal Performance in Indonesia: Mediating Role of Supply Chain Practices - Ekosusilo, Madyo (International Journal of Supply Chain Management, 2020)
Abstract- The prime aim related to the existing research is to examine the impact of organizational culture, work motivation, compensation on job satisfaction on school principal performance in the Indonesian school system. The secondary aim associated with this literature is to investigate the mediating role of supply chain practices (SCP) among the links of organizational culture and performance of school principal, compensation on job satisfaction and performance of school principal and work motivation and performance of school principal. For analysis purposes data were gathered from the private schools that are currently operating in Indonesia and PLS-SEM was employed to test the hypotheses that are purposed by the research. The results indicated that positive links among the organizational culture, work motivation, compensation on job satisfaction and school principal performance. The outcomes also indicated that SCP has positively mediated among the nexus of organizational culture and performance of school principal, compensation on job satisfaction and performance of school principal and work motivation and performance of school principal. The research gives insight to the regulators that they expand their focus on the organizational culture along with the work motivation and job satisfaction that enhance the performance of the principal in the school.